Promising high-yielding tetraploid plantain-bred hybrids in west Africa - Tenkouano, A.; Lamien, Niéyidouba; Agogbua, J.; Amah, D.; Swennen, Rony L.; Traoré, S.; Thiemele, D.; Aby, N.; Kobenan, K.; Gnonhouri, G.; Yao, N.; Astin, G.; et al. (Hindawi Limited, 2019)
The devastating threat of black leaf streak disease caused by Pseudocercospora fijiensis on plantain production in West Africa spurred the development of resistant hybrids. The goal of this research and development (R&D) undertaken was assessing the development and dissemination of two plantain hybrids PITA 3 and FHIA 21 bred in the 1980s by the International Institute of Tropical Agriculture (IITA, Nigeria) and the Fundación Hondureña de Investigación Agrícola (FHIA, Honduras), respectively. In Côte d’Ivoire, plantain growers selected PITA 3 and FHIA 21 based on their improved agronomic characteristics and, between 2012 and 2016, they were massively propagated and distributed to farmers in Benin, Burkina Faso, Côte d’Ivoire, and Togo under the West Africa Agricultural Productivity Program (WAAAP) coordinated by the West and Central Africa Council for Agricultural Research and Development (CORAF). In 2016, the Centre National de Recherche Agronomique in Côte d’Ivoire included the hybrids in the improved cultivar directory. This R&D activity illustrates how three decades of crossbreeding, selection, and distribution led to local acceptance. It also highlights how a CORAF-led partnership harnessed CGIAR research for development. The dissemination and acceptance of these plantain hybrids will enhance the sustainable intensification in plantain-based farming systems across the humid lowlands of West and Central Africa.